Potential of Propolis In Hard Candy and Related Oral Delivery Systems for Dental and Oral Health: A Systematic Review - Wiwekowati; Ketut Virtika Ayu; Norman Hidajah (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2026)
Introduction: Dental and oral diseases remain major global health problems. Although propolis has antimicrobial, anti-inflammatory, and antioxidant properties, evidence regarding its use as a prolonged oral drug delivery system remains limited. No systematic review has specifically evaluated propolis hard candy as an oral delivery platform. This review aimed to synthesize evidence on propolis hard candy and related prolonged oral delivery systems for dental and oral health. Review: This systematic review followed PRISMA 2020 guidelines. PubMed, Scopus, and Google Scholar were searched for studies published from January 2014 to March 2025. Eligible studies included randomized controlled trials, clinical studies, in vivo animal studies, and in vitro experiments evaluating propolis or related oral delivery systems. Two reviewers independently performed study selection, data extraction, and quality assessment using Cochrane RoB 2, the Newcastle–Ottawa Scale, and a modified checklist. Of 337 records, 10 studies met the eligibility criteria. In vitro studies demonstrated inhibition of Streptococcus mutans biofilm formation and Candida albicans growth, while solid oral delivery systems provided prolonged retention and sustained release. Clinical and in vivo studies indicated improved gingival health and anti-inflammatory effects, although evidence was limited by moderate risk of bias, small samples, and short follow-up. Conclusion: Propolis hard candy shows promise as an adjunctive oral drug delivery platform, but direct clinical evidence remains insufficient. Well-designed, double-blind randomized controlled trials using standardized formulations are needed to establish its efficacy, safety, and clinical advantages.